Quality Control of Long-Lasting Insecticidal Nets: Are We Neglecting It?. Issue 7 (July 2021) - Karl, Stephan; Katusele, Michelle; Freeman, Timothy W.; Moore, Sarah J.
Abstract : Over 2.2 billion long-lasting insecticidal nets (LLINs) for malaria control have been delivered to recipient countries. LLINs are the largest single item in the global malaria control budget. To be eligible for donor-funded procurement and distribution schemes, LLIN products must attain and retain World Health Organization (WHO) prequalification status by passing safety, quality, and efficacy benchmarks. Predelivery inspections further test product quality before distribution. We have shown that, despite these quality-assurance measures, substandard LLINs were distributed in Papua New Guinea (PNG) for at least 6 years (2013–2019). Other countries may have received similar LLINs. Here, we discuss the most important weaknesses of the current LLIN quality-assurance framework that have made this possible. Highlights: Based on a series of concerning observations of a sudden decrease in the bioefficacy of long-lasting insecticidal nets (LLINs) in Papua New Guinea in 2013, we discuss the urgent need for a revision of the framework for the quality assessment of LLINs for both prequalification (PQ) purposes and post-PQ monitoring. The most important deficiencies of the current system include the absence of regular bioefficacy assessment for quality assurance, the ambivalence of the currently recommended bioassay methodologies, and the lack of capacity in many recipient countries for basic LLIN quality assurance. It is in the interest of manufacturers, donors, recipient countries, and most importantly, those relying on LLINs for protection against malaria, that the quality-assurance framework for these important commodities remains rigorous, adaptive, and transparent.